New evidence on the development of Australian refugee policy, 1976 to 1983 - Higgins, C; Claire Michelle Higgins (2013)
This thesis aims to improve historical knowledge of Australian refugee policy between 1976 and 1983, a unique and transitional moment in the nation’s history and in international refugee movements. The discussion will be based on original evidence drawn from archival records and oral history interviews, and informed by a broad literature which recognises that refugee policy is a product of varied political imperatives and historical context. First, Chapter Three reveals that because the Fraser government could not deport the Indochinese boatpeople who sailed to Australia, it sought to approve their refugee status in order to legitimate its announcements that only ‘genuine’ refugees were being admitted. In doing so, the Fraser government was required to defend the processing of boat arrivals to the public and within the bureaucracy. Chapter Four finds that historical and political considerations informed the Fraser government’s choice not to reject or detain boat arrivals but to instead introduce legislation against people smuggling. The chapter presents new evidence to disprove claims expressed in recent academic and media commentary that the government’s Immigration (Unauthorised Arrivals) Act 1980 (Cth) marked a particularly harsh stance and that passengers on the VT838 were deported without due process, and draws from ideas within the literature concerning the need for states to promote the integrity of the refugee concept. Chapter Five contributes to international literature on refugee status determination procedure by studying the Australian government’s assessment of non-Indochinese. Through a dataset created from UNHCR archives it is found that the quality of briefing material and political considerations could influence deliberations on individual cases. Chapter Six contributes to literature on in-country processing, revealing how Australia’s programme in Chile and El Salvador was a means of diversifying the refugee intake but caused tensions between the Department of Immigration and the Department of Foreign Affairs.